2017
DOI: 10.21276/apalm.1393
|View full text |Cite
|
Sign up to set email alerts
|

Variant Hemoglobin Spectrum By Cation Exchange High Performance Liquid Chromatography: A Study 0f 2035 Subjects

Abstract: Introduction: Hemoglobinopathies and thalassemia are hereditary disorders of hemoglobin (Hb) affecting mankind at prevalent regional level. Automated cation exchange high performance liquid chromatography is being increasingly used as the initial diagnostic method for identifying normal and abnormal hemoglobin variants. Methodology:Total 2035 sample received and studied. All samples run on cation exchange high performance liquid chromatography machine by BIO-RAD.Results: Total 386(18.96%) cases had abnormal he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…In our study the prevalence for sickle cell trait was found out to be 4.7%, which is very much comparable with the study done by Sarvaiya et al 13 which showed a prevalence of 4.71%. But other studies showed a relatively less prevalence like Buch et al 3 who had done a study on 3465 patients in Pune and quoted a prevalence of 0.2%.…”
Section: Sickle Cell Traitsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study the prevalence for sickle cell trait was found out to be 4.7%, which is very much comparable with the study done by Sarvaiya et al 13 which showed a prevalence of 4.71%. But other studies showed a relatively less prevalence like Buch et al 3 who had done a study on 3465 patients in Pune and quoted a prevalence of 0.2%.…”
Section: Sickle Cell Traitsupporting
confidence: 91%
“…In the present study prevalence for Sickle-thalassemia was found out to be 0.94% which is comparable to the study done by Shrivastav et al 15 , Baruah et al 14 and Sarvaiya et al 13 quoting a prevalence of 0.72%, 0.59% and 0.68% respectively. We did not find any case of other abnormal hemoglobins such as HbE, HbD, HbC, HbQ and other double heterozygous in our study.…”
Section: Double Heterozygous For Sickle-thalassemiasupporting
confidence: 89%
See 2 more Smart Citations
“…The third most commonest hemoglobinopathy that was detected in the total population of 29,293 patients within the 14 studies was of Hb E. Hb E constituted about 18.9% of hemoglobinopathies. Except for the reports of Sachdev et al [ 1 ], Shrivastav et al [ 3 ], Bhalodia et al [ 6 ], Sarvaiya and Chauhan [ 10 ], Shankar et al [ 12 ], and Jain and Saxena [ 13 ], Hb E remained the third most common hemoglobin variant detected.…”
Section: Reviewmentioning
confidence: 99%